The Consensual Divorce (ṭalāq) in Palestine - Polfus, Turid Smith (Hawwa, 2024)
Most divorces in Palestine come about through a private unregulated agreement between the spouses referred to as “ṭalāq bit-taradi” (consensual ṭalāq), often called mukhalaʿa or mubāraʾa. Over the last century, women’s economic rights in the unilateral ṭalāq have increased. At the same time, the number of consensual ṭalāq has risen. While the consensual ṭalāq provides a way out of an unwanted marriage for women, it hardly represents a form of ‘gender equality’. Rather, it is a field where kin-patriarchy is asserting itself through women’s dependence on agnates to reach an agreement and to bear the cost of such divorces. Furthermore, the consensual ṭalāq invites abuse and economic extortion from husbands. As the Islamic shariʿa court condemns such behaviour, our study nevertheless finds that the court facilitates the consensual ṭalāq by setting the bar for litigated divorce too high and by letting time pass.